Lighting the Way: Qur’an Verses on Education in Mathematical Representation - Ahmad, Andi Kamal; Hasyim Haddade; Nur Jihadilla; Hamkah; Abdul Hakim Junaid (Journal of Practice Learning and Educational Development, 2025)
This research aims to develop a mathematical model of the representation of Qur’an verses about education. Partially, the study examines the epistemology of Qur’an education based on educational aspects and indicators, relevant educational concepts in the Qur'an, and mathematical models to analyze the relationship between Qur'an-based education qualitatively and quantitatively. The results of this study offer a new quantitative analytical framework for Qur’an education, a structured Islamic curriculum development tool, the potential to improve the quality of evaluation of Islamic education programs through quantitative metrics, interdisciplinary collaboration opportunities, and a unique perspective from Islamic traditions for global education discourse. This research is new because it applies mathematical modelling to the epistemology of the Qur'an (not yet exists), uses a quantitative approach in the study of Qur’an education (generally qualitative), and integrates religious epistemology with scientific methodology. The research gap lies in the lack of a quantitative approach and exploration of structured Qur’an education epistemology, as well as the lack of bridges between religious theory and modern educational practice. The latest Islamic education research trends focus on the integration of Islamic values, the development of Islamic learning models, the analysis of character thoughts, and character studies. Recommendations include exploration of the potential of mathematical modelling by researchers in Islamic education and mathematics, consideration of the use of models in curriculum development and evaluation by Islamic educational institutions, as well as the expansion of the model with other variables and empirical testing in subsequent research.